A rare case of dual congenital coronary cameral fistula and myocardial bridge: A case report. Issue 16 (22nd April 2022) - Shen, Yong
Abstract: Rationale: A coronary artery fistula (CAF) is an anomalous communication between a coronary artery and a cardiac chamber or great vessel. It is a rare congenital anomaly that is often small and asymptomatic, occurring in only 0.002% of the general population. Most CAFs originate from the right coronary artery and flow into the right cardiac system. Although extremely rare, some cases may originate from the bilateral coronary arteries and flow into the left ventricle. Patient concerns: Herein, we report a rare case of a 55-year-old male smoker with no history of heart disease or cardiac surgery, who presented with a 5-year history of recurrent chest congestion, palpitations, and shortness of breath. On physical examination, his heart and lungs revealed normal findings without cardiac murmurs and no systemic or pulmonary edema. Moreover, 24-hour ambulatory electrocardiography showed no signs of ischemia but exhibited a short array of ventricular tachycardia and short atrial tachycardia. Chest computed tomography showed left apical emphysema without cardiomegaly and pulmonary congestion. Furthermore, coronary angiography revealed dual congenital coronary cameral fistula, a complex CAF with a left circumflex artery–left ventricle fistula and a right coronary artery–left ventricle fistula, complicated with a myocardial bridge. Diagnosis and interventions: A diagnosis of left circumflex artery–left ventricle fistula complicated with a right coronary artery–left ventricle fistula and myocardial bridge was made. Since the patient refused surgery, medical management with enteric-coated aspirin, sustained-release metoprolol, and atorvastatin calcium was initiated. Outcomes and lesson: Currently, the patient is now asymptomatic and in good condition since 6 months after undergoing conservative treatment with β-blockers.